Structural Insights into Interaction between Mammalian Methionine Sulfoxide Reductase B1 and Thioredoxin. (13th March 2012) - Dobrovolska, Olena; Rychkov, Georgy; Shumilina, Elena; Nerinovski, Kirill; Schmidt, Alexander; Shabalin, Konstantin; Yakimov, Alexander; Dikiy, Alexander
Abstract : Maintenance of the cellular redox balance has vital importance for correcting organism functioning. Methionine sulfoxide reductases (Msrs) are among the key members of the cellular antioxidant defence system. To work properly, methionine sulfoxide reductases need to be reduced by their biological partner, thioredoxin (Trx). This process, according to the available kinetic data, represents the slowest step in the Msrs catalytic cycle. In the present paper, we investigated structural aspects of the intermolecular complex formation between mammalian MsrB1 and Trx. NMR spectroscopy and biocomputing were the two mostly used through the research approaches. The formation of NMR detectable MsrB1/Trx complex was monitored and studied in attempt to understand MsrB1 reduction mechanism. Using NMR data, molecular mechanics, protein docking, and molecular dynamics simulations, it was found that intermediate MsrB1/Trx complex is stabilized by interprotein β -layer. The complex formation accompanied by distortion of disulfide bond within MsrB1 facilitates the reduction of oxidized MsrB1 as it is evidenced by the obtained data.